2011
DOI: 10.1371/journal.ppat.1001279
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping Identifies Novel Highly Protective Antigens for an Apicomplexan Parasite

Abstract: Apicomplexan parasites are responsible for a myriad of diseases in humans and livestock; yet despite intensive effort, development of effective sub-unit vaccines remains a long-term goal. Antigenic complexity and our inability to identify protective antigens from the pool that induce response are serious challenges in the development of new vaccines. Using a combination of parasite genetics and selective barriers with population-based genetic fingerprinting, we have identified that immunity against the most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 30 publications
8
97
0
Order By: Relevance
“…revealed significant strain-specific variation and some lack of heterologous immunoprotection, although the breakthrough in parasite replication was at a level unlikely to lead to occurrence of clinical disease (39). Antigenic diversity has been described elsewhere for E. tenella (40), albeit at a much lower level than reported for species such as E. maxima and Eimeria acervulina (14,41,42). The relevance of these findings to the other Eimeria species that infect poultry is not currently clear.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…revealed significant strain-specific variation and some lack of heterologous immunoprotection, although the breakthrough in parasite replication was at a level unlikely to lead to occurrence of clinical disease (39). Antigenic diversity has been described elsewhere for E. tenella (40), albeit at a much lower level than reported for species such as E. maxima and Eimeria acervulina (14,41,42). The relevance of these findings to the other Eimeria species that infect poultry is not currently clear.…”
Section: Discussionmentioning
confidence: 83%
“…As recombinant or vectored subunit anticoccidial vaccines become technically more feasible, the regional occurrence of each Eimeria species and the extent of vaccine-targeted antigenic diversity assume greater relevance (5,14). Under experimental conditions, studies with clonal reference strains of Eimeria have found antigens such as AMA1 to induce good levels of immunoprotection (14,26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations